Next-generation sequencing-based comparative mapping and culture-based screening of bacterial rhizobiome in Phytophthora capsici-resistant and susceptible Piper species - Hima Parvathy, A.; Santhoshkumar, R.; Soniya, E. V. (Frontiers in Microbiology, 2024)
Black pepper (Piper nigrum L.), a highly valued spice crop, is economically significant as one of the most widely traded spices in the world. Global yield and quality of black pepper (Piper nigrum L.) is affected by foot rot causing soil-borne oomycete pathogen Phytophthora capsici. To gain initial insights towards developing an approach that utilises microbial genetic resources for controlling foot rot disease in black pepper, we mapped the rhizobiome communities in susceptible Piper nigrum L. and wild resistant Piper colubrinum. Analysis showed compositional differences in rhizobiome of two Piper species which revealed higher diversity and presence of more differentially abundant genera in P.colubrinum. Further, P. colubrinum rhizobiome had significantly higher abundance of known anti-oomycete genera, such as Pseudomonas, and higher differential abundance of Janthinobacterium, Variovorax and Comamonas indicating their probable contribution to pathogen resistance. Predictive functional profiling in P. colubrinum rhizobiome showed highly enriched functional gene orthologs (KOs) particularly chemotaxis proteins, osmoprotectants, and other transport systems that aid in pathogen resistance. Similarly, pathways such as phenylpropanoid biosynthesis and other antimicrobial synthesis were enriched in P.colubrinum rhizobiome. The culturable diversity of the resistant root endosphere which harbours efficient biocontrol agents such as Pseudomonas strengthens the possible role of root microbiome in conferring resistance against soil borne pathogens. Taken together, our results depicted a clear distinction in the rhizobiome architecture of resistant and susceptible Piper spp. suggesting its influence in recruiting bacterial communities that probably contributes in pathogen resistance.